2012
DOI: 10.7845/kjm.2012.48.1.022
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Plasmid Profile of Vibrio parahaemolyticus Strains Isolated from Kyunggi-Incheon Coastal Area

Abstract: Vibrio parahaemolyticus is one of the major agents responsible for food poisoning during summer in Korea, which is transmitted via seawater or seafoods. Recently, distribution of the bacteria in the marine environment has been increased due to global warming. Great concern also has been raised regarding public hygiene as well as marine culture by the emergence of pathogens with antibiotic resistance. Therefore, distribution of V. parahaemolyticus and antibiotic resistance of the isolates were monitored in 7 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Another study was conducted in samples (n = 685) of fish and shellfish collected from retail seafood markets in Kyunggi province and Incheon city, Korea. In that study, the monthly detection rate of V. parahaemolyticus ranged from 30.5 to 61.5%; the highest level was found in August (Han et al 2012).…”
Section: Distribution Of V Parahaemolyticus In Fish and Shellfishmentioning
confidence: 76%
See 2 more Smart Citations
“…Another study was conducted in samples (n = 685) of fish and shellfish collected from retail seafood markets in Kyunggi province and Incheon city, Korea. In that study, the monthly detection rate of V. parahaemolyticus ranged from 30.5 to 61.5%; the highest level was found in August (Han et al 2012).…”
Section: Distribution Of V Parahaemolyticus In Fish and Shellfishmentioning
confidence: 76%
“…In some reported results, V. parahaemolyticus was enumerated by the most probable number method. Han et al (2012) investigated the abundance of V. parahaemolyticus in 281 seawater samples collected from the west coast of Korea (Kyunggi province and Incheon city). According to their results, the level of V. parahaemolyticus was high in summer, especially in August (92.9%) followed by July (85.0%) and September (76.5%).…”
Section: Distribution Of V Parahaemolyticus Isolates On the Korean Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports performed in South Korea showed the antibiotic susceptibility profile of V. parahaemolyticus isolates in seawater samples and found that 3.0–12.2% of isolates were resistant to tetracycline and ciprofloxacin, respectively ( Son et al, 2005 ; Kim et al, 2014 ). Other studies reported using different antibiotics against V. parahaemolyticus for detecting antibiotic susceptibility ( Han et al, 2012 ; Yang J. H. et al, 2017 ; Park et al, 2018 ). Most of the antimicrobials tested in this study are using in agriculture and aquaculture fields ( Kim S. et al, 2016 ; Kang et al, 2017 ), as well as in the treatment of vibrio infections ( Shaw et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…장염비브리오의 항균제 내성 양상 amikacin, ampicillin, cephalothin, cefoxitin, gentamicin, kanamycin, rifampin, streptomycin vancomycin (Son et al, 2005;Lee et al, 2009;Ryu et al, 2010;Han et al, 2012;Kim et al, 2014;Kang et al, 2016;Kim et al, 2016 (Tanil et al, 2005;Lee et al, 2009;Lee and Park, 2010;Kim et al, 2014). Clindamycin MIC 16.0 µg/…”
Section: Trh (mentioning
confidence: 99%